Water-assisted self-healing and property recovery in a natural dermal armor of pangolin scales. (March 2016) - Liu, Z.Q.; Jiao, D.; Weng, Z.Y.; Zhang, Z.F.
Abstract: Self-healing capacity, of which the inspiration comes from biological systems, is significant for restoring the mechanical properties of materials by autonomically repairing damages. Clarifying the naturally occurring self-healing behaviors and mechanisms may provide valuable inspiration for designing synthetic self-healing materials. In this study, water-assisted self-healing behavior was revealed in a natural dermal armor of pangolin scales. The indentation damages which imitate the injury caused by predatory attack can be continuously mitigated through hydration. The healing kinetics was characterized according to the variations of indentation crater dimension and quantitatively described in terms of the viscoelastic behavior of biopolymer. The mechanical properties of original, damaged, and recovered scales in both dry and wet states were systematically evaluated by three-point bending and compared through statistical analysis. The hydration effects and mechanisms were explored by examining the dynamic mechanical properties and thermal behaviors. The promoted self-healing process can be attributed to the improved flexibility of macromolecules in the biopolymer. This study may stimulate useful self-healing strategies in bio-inspired design and aid in developing high-performance synthetic self-healing materials. Graphical abstract: Highlights: Water-assisted self-healing behavior was revealed in biopolymer of pangolin scales. Indentation crater and microscopic damages can be diminished by hydration. Healing kinetics was quantitatively described in terms of viscoelastic behavior. Both strength and reliability can be recovered through water-assisted self-healing. Accelerated self-healing was attributed to improved flexibility of macromolecules.